Prevalence of Helicobater pylori Among Suspected Ulcer Patients Attending General Hospital Wukari, Taraba State - Brown, Samuel Tamunoiyowuna Cockeye; Mohammed, Ikrimah Usman; Umaru, Isaac John; Mijinyawa, Ibrahim Jamilat; Daniel, Benjamin Nanisi; Melvin, Ugwuala Chimaobi; Abdulkadir, Nurudeen Umar (African Journal of Clinical Medicine and Pharmacy Research, 2024)
H. pylori are microaerophilic organism and a Gram negative bacterium which is found in the alimentary canal. It causes chronic gastritis and gastric ulcers. It is also linked to the development of duodenal ulcers and stomach cancer, conditions that were not previously believed to have a microbial cause. These study aim to determine the prevalence of Helicobacter pylori infection among suspected peptic ulcer patients attending General Hospital Wukari, Nigeria. A total of one hundred (100) blood samples were collected from consenting patient attending General Hospital, Wukari. Demographic information such as age and sex of each participant was obtained. Blood samples were collected by venipuncture. 5mL of blood was collected from each patient into well labelled ethylene diamine tetraacetic acid (EDTA) vacutainer tube. The Rapid Test kit was used for the qualitative detection of H. pylori surface antigen in serum/plasma. It utilises a combination of monoclonal and polyclonal antibodies to selectively detect elevated levels of H. pylori in serum/plasma. Consenting patients who participated in the study were between the age ranges of 1 to 95 years. Total prevalence of H. pylori was observed is 66%. The male gender was more infected with H. pylori infection 71.9% than the female counterparts with 58.13%. Out of the total patients 66% of the study patients tested positive for H. pylori. Among them, 60% were male and 40% were female. The age breakdown showed most patients were between 16-35 years old. It shows that the prevalence of H. pylori infection by sex among outpatient which 60% of the patients were male while 40% were female. With this the prevalence of H. pylori infection among patients attending General Hospital Wukari is 66%. Despite the high prevalence of H. pylori infection among the study subjects, these infections are threats to the human health. Hence, strategies should be adopted to help combat and control these infections and their spread within the population.